Game and Song Integration as Vocabulary Learning Tools for EFL Students: A Systematic Review - Sitompul, Surya Habibi; Ahmad, Hafiz Aziz; Sulistyaningtyas, Tri (Salingka, 2025)
This study investigates the integration of songs and games in English vocabulary learning, using the Systematic Literature Review (SLR) method. Relevant literature was reviewed from data sources such as Scopus and ScienceDirect using Boolean keywords structured as prompts to narrow down focused data. This study aims to identify previous research that discusses the role of songs and games in English language learning, particularly in vocabulary acquisition. The selected relevant studies were then analyzed to understand the learning mechanisms applied and how effective these mechanisms are in supporting the English learning process for EFL students. This study resulted in 20 articles; however, not all describe the mechanisms of song-based games in detail, as they only mention possible approaches or strategies applied in English learning. The approach used is Multimodal Learning (MML), which incorporates visual, auditory, textual, and kinesthetic elements. This is supported by game elements such as rewards and punishments, points or scores, challenges, and feedback to enhance student engagement and retention.